Once & future. Volume five, The wasteland - Gillen, Kieron (BOOM! Studios, 2023)
"It's the day before Christmas and the Kings all converge on Excalibur, each determined to be the true ruler. Chaos arises! What if no one has the strength to take the sword? Will there finally be peace after so much conflict, or will an unexpected figure claim the throne? Rituals, bombs, and battles ensue, while the final fate of Mary, Rose, Bridgette, Merlin, and the rest awaits!--